MODELS OF ORGANIZING INDEPENDENT STUDY OF STUDENTS - Aripova, Sh. (SCIENCE and SOCIETY, 2022)
Based on the analysis of scientific and methodological literature, the article actualizes the problem of organizing independent work of students at the present stage of education development, considers new functions and roles of a higher school teacher and suggests the main ways to stimulate and support independent work of students in the educational process.
Keywords: independent study; model of organization of independent work of students; pedagogical style; information; tutoring